Weld material for cast iron repair and repair method

JP2025026372APending Publication Date: 2025-02-21MITSUI E&S CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2024127807
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-09
Filing Date
2024-08-02
Publication Date
2025-02-21

AI Technical Summary

Benefits of technology

【0017】 本発明によれば、溶接部周辺あるいは近傍の鋳鉄母材の熱影響部のミクロ組織を改善し、機械的特性を改善することができる鋳鉄補修用溶接材料及び補修方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025026372000004
    Figure 2025026372000004
  • Figure 2025026372000005
    Figure 2025026372000005
  • Figure 2025026372000006
    Figure 2025026372000006
Patent Text Reader

Abstract

To provide a weld material for cast iron repair and a repair method capable of improving a micro structure of a heat affected part of a cast iron base material in the periphery or vicinity of a weld part and improving a mechanical characteristic.SOLUTION: Provided is a weld material for repair weld of a member made of cast iron that is a weld material for cast iron repair containing at least Ni, Cr, Mn, and Nb, preferably, a weld material for cast iron repair containing 10.0 to 30.0 mass% of Cr, 1.0 to 10.0 mass% of Mn, 2.0 to 3.0 mass% of Nb, and the balance Ni with inevitable components.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a welding material for repairing cast iron and a repair method, and more particularly to a welding material for repairing cast iron and a repair method capable of improving the microstructure of a heat-affected zone and improving the mechanical properties of a repair welded portion. [Background technology]

[0002] Cast iron has excellent properties such as wear resistance and vibration absorption, as well as low solidification shrinkage and melting point, excellent fluidity, and good castability, so it is widely used in fields such as automobiles, ships, and various industrial machines. However, cast iron is generally known as a material that is difficult to weld, and when defects are found in cast iron components, they are often discarded and remanufactured without being repaired by welding.

[0003] The reason why cast iron is difficult to weld is because of its high carbon (graphite) content of 2.5-4.5 mass%. The heat generated during welding changes the graphite into a brittle cementite phase (iron carbide, Fe3C), making it susceptible to cracking.

[0004] In order to avoid such problems, it is effective to add elements that destabilize the cementite phase, and Ni is one of the elements that has such an effect. Therefore, conventional welding materials for repairing cast iron are generally pure Ni-based or Ni-Fe-based.

[0005] The tensile strength of the weld metal alone of pure Ni-based welding materials is only just over 300 MPa. Therefore, when the strength of the cast iron base material increases, the strength of the welding material becomes relatively low, raising concerns about a strength mismatch and limiting the range of base material options.

[0006] In addition, Ni-Fe welding materials are somewhat stronger than pure Ni welding materials, but have a lower effect of destabilizing the cementite phase than pure Ni welding materials, which makes them more susceptible to cracking during welding.As a result, when they are made into welded joints, cracks tend to propagate from the weak fusion boundary, and the tensile strength is often not as strong as that of the weld metal alone. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2017-74602 A [Patent Document 2] Japanese Patent Application Publication No. 8-90238 Summary of the Invention [Problem to be solved by the invention]

[0008] Patent Document 1 proposes that, from the viewpoint of preventing the formation of cementite, even when cast iron is welded using Ni-Fe based welding material, cementite with poor ductility is formed near the fusion boundary of the weld due to high heat input during welding, which may reduce the weld strength. In response to this problem, the content of C and Si in the composition of the Ni-Fe based welding material is specified, and the weld is post-heat-treated to graphitize the cementite, thereby improving the strength of the weld metal and preventing the occurrence of cracks. However, simply graphitizing the cementite is not sufficient to improve the microstructure.

[0009] Patent Document 2 points out that when cast iron is welded, ledeburite (a eutectic structure of austenite and cementite) crystallizes around the eutectic between the weld metal and the base metal heat-affected zone, and weld cracks occur in this area, and therefore, when welding cast iron, a challenge is how to suppress the generation of ledeburite in two locations, the weld metal and the base metal heat-affected zone.

[0010] One method of welding cast iron is to use a welding rod made of Ni or similar material. The purpose of using a welding rod made of Ni or similar material is to reduce the heat input to the heat-affected zone of the base material to reduce the crystallization of ledeburite around the eutectic, and to increase the toughness of the weld metal by adding Ni to prevent cracking. However, it is not possible to prevent the crystallization of ledeburite itself, and ledeburite is still firmly present in the microstructure after welding.

[0011] In the welding of cast iron in Patent Document 2, it is acknowledged that the amount of ledeburite generated cannot be reduced, and the idea is that it is satisfactory as long as there are no cracks, but there is a problem in that the problem of the microstructure cannot be fundamentally solved.

[0012] The present inventors have focused on a welding material and a repair method that exhibit physical properties such as high tensile strength and elongation at the fusion boundary of a joint in cast iron welding and can realize an improvement in the microstructure, and have completed the present invention through intensive research.

[0013] That is, an object of the present invention is to provide a welding material for repairing cast iron and a repair method capable of improving the microstructure of the heat-affected zone of the cast iron base metal around or in the vicinity of the weld and improving the mechanical properties.

[0014] Further objects of the present invention will become apparent from the following description. [Means for solving the problem]

[0015] The above problems are solved by the following inventions.

[0016] 1. A welding material for repair welding of cast iron members, A welding material for repairing cast iron containing at least Ni, Cr, Mn and Nb. 2. 2. The welding material for repairing cast iron according to item 1, characterized in that it is composed of 10.0-30.0 mass % of Cr, 1.0-10.0 mass % of Mn, 2.0-3.0 mass % of Nb, and the balance being Ni and unavoidable components. 3. 3. The welding material for repairing cast iron according to 2 above, containing 6.0 mass % or less of Si and 2.0 mass % or less of Al as optional added elements. 4. 4. A repair method comprising repair welding of a cast iron member using the welding material for repairing cast iron according to claim 1, 2 or 3. 5. 5. The repair method according to item 4, wherein the repair welding is build-up repair or backing plate repair. 6. 5. The repair method according to item 4, characterized in that in the microstructure of the heat-affected zone around the weld, the area ratio of pearlite is increased and the amount of ledeburite generated is reduced. Effect of the Invention

[0017] According to the present invention, it is possible to provide a welding material for repairing cast iron and a repair method that can improve the microstructure of the heat-affected zone of the cast iron base material around or in the vicinity of the weld and improve the mechanical properties. [Brief description of the drawings]

[0018] [Figure 1] Schematic cross-sectional view of a weld formed by overlay repair on a cast iron base material [Diagram 2] Schematic cross-sectional view of a weld formed by repairing a cast iron base material with a patch plate [Diagram 3] 1 is a high-magnification optical microscope photograph showing a detailed microstructure in the heat-affected zone around the weld in Example 1. [Figure 4] 1 is a low-magnification optical microscope photograph showing the main microstructure in the heat-affected zone around the weld in Example 1. [Diagram 5] 1 is a high magnification optical microscope photograph showing detailed microstructure in the heat affected zone around the weld in Example 2. [Figure 6] 1 is a low-magnification optical microscope photograph showing the main microstructure in the heat-affected zone around the weld in Example 2. [Figure 7]1 is a high magnification optical microscope photograph showing detailed microstructure in the heat affected zone around the weld in Example 3. [Figure 8] 1 is a low-magnification optical microscope photograph showing the main microstructure in the heat-affected zone around the weld in Example 3. [Figure 9] 1 is a high magnification optical microscope photograph showing detailed microstructure in the heat affected zone around the weld in Example 4. [Figure 10] 1 is a low-magnification optical microscope photograph showing the main microstructure in the heat-affected zone around the weld in Example 4. [Figure 11] 1 is a high magnification optical microscope photograph showing detailed microstructure in the heat affected zone around the weld in Example 5. [Figure 12] 1 is a low-magnification optical microscope photograph showing the main microstructure in the heat-affected zone around the weld in Example 5. [Figure 13] 1 is a high-magnification optical microscope photograph showing a detailed microstructure in the heat-affected zone around the weld in Comparative Example 1. [Figure 14] 1 is a low-magnification optical microscope photograph showing the main microstructure in the heat-affected zone around the weld in Comparative Example 1. [Figure 15] 1 is a high-magnification optical microscope photograph showing a detailed microstructure in the heat-affected zone around the weld in Comparative Example 2. [Figure 16] 1 is a low-magnification optical microscope photograph showing the main microstructure in the heat-affected zone around the weld in Comparative Example 2. [Figure 17] Graph showing tissue occupancy (area ratio) in each detailed tissue site of Example 1, Example 2, Example 3, Example 4, Example 5, Comparative Example 1, and Comparative Example 2 [Figure 18] Graph showing average thickness in each subject tissue site of Example 1, Example 2, Example 3, Example 4, Example 5, Comparative Example 1, and Comparative Example 2 DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Preferred embodiments of the present invention will now be described.

[0020] 1 and 2 are schematic cross-sectional views of a welded portion where a cast iron base material has been repaired by welding using a welding material. FIG. 1 shows an example of build-up repair, and FIG. 2 shows an example of backing plate repair. Examples of repair methods using repair welding to repair cast iron base material include build-up repair, in which the defect is removed and a welding material is build-up welded onto the removed area, and backing plate repair, in which a backing plate is attached by fillet welding without removing the defect. Fig. 1 shows an example of build-up repair in which a groove is formed at a repair location in base metal 11, and welding material 12 is filled into the gap in the trapezoidal groove to form a weld 13. Also, Fig. 2 shows an example of backing plate repair in which a defect 15 is covered with a backing plate 16, and the periphery of the backing plate 16 is fillet welded with the welding material 12 to form a weld 13. In Figs. 1 and 2, reference numeral 14 denotes a weld boundary between the base metal 11 made of cast iron and the welding material 12.

[0021] A heat-affected zone exists on the base metal side of the weld boundary 14. The heat is due to heat input caused by welding. The weld 13 is formed by overlay repair with the welding material 12 at the weld boundary 14. The weld 13 may be formed by laminating the welding material 12. The shape of the groove is not limited to a V-shape including a trapezoidal groove as shown in FIG. 1, but may be a U-shape, a R-shape, a J-shape, etc., and is appropriately selected taking into consideration the thickness of the base material, the welding method, and the shape and range of the defect to be removed.

[0022] The welding method for repairing and welding the gap in the groove with the welding material 12 is not particularly limited, but examples thereof include laser welding and arc welding. Examples of arc welding include gas tungsten arc welding (GTAW), shielded metal arc welding (SMAW), and gas metal arc welding (GMAW). Among these, gas tungsten arc welding (GTAW) is preferable.

[0023] The base material to which the present invention can be applied is not particularly limited, but includes cast iron base materials and components that require mechanical properties equivalent to those of cast iron base materials, such as reciprocating compressors and internal combustion engines that are configured with cast iron cylinders.

[0024] The welding material of the present invention is preferably used when the base materials are both cast iron members (for example, both spheroidal graphite cast iron members).

[0025] The welding material in the present invention may be a welding material as shown in FIG. 1, a welding rod, or a welding wire.

[0026] In order to satisfactorily achieve the effects of the present invention, the welding material of the present invention is a welding material for repair welding of cast iron members, and may be a welding material for repairing cast iron that contains at least Ni, Cr, Mn, and Nb.

[0027] The welding material of the present invention preferably contains at least Ni, Cr, Mn and Nb as constituent elements, which can improve the microstructure of the heat-affected zone around the weld and improve the mechanical properties of the heat-affected zone caused by repair welding.

[0028] The welding material preferably contains 10.0 to 30.0 mass % of Cr, 1.0 to 10.0 mass % of Mn, 2.0 to 3.0 mass % of Nb, and the balance being Ni and unavoidable components.

[0029] Ni is an element that promotes graphitization of carbon (C) and does not form carbides, so it is unlikely to form a brittle phase during welding, and is a main constituent element of welding materials for cast iron. The Ni content is the balance of the welding material, and is preferably at least 60 mass%, more preferably in the range of 60 to 87 mass%.

[0030] Cr shifts the pearlite transformation to the high temperature and short time side in the continuous cooling transformation curve of spheroidal graphite cast iron, and increases the amount of pearlite formed, thereby contributing to improving the strength of the base metal. In addition, Cr lowers the martensite transformation start temperature, suppressing martensite formation and reducing the risk of weld cracks. However, if the Cr content exceeds 30.0 mass%, the risk of weld cracks increases due to a decrease in the ductility of the weld metal itself, and if it is below 10.0 mass%, the metallic luster of the bead surface is lost due to oxidation. Therefore, the Cr content is preferably in the range of 10.0 to 30.0 mass%, and more preferably in the range of 10.0 to 20.0 mass%.

[0031] Mn has the effect of increasing the pearlite area ratio in the heat-affected zone around the weld, and therefore contributes to improving the strength of the base material. It can be seen that the inclusion of Mn in the welding material improves the pearlite area ratio in the microstructure. The improvement in the pearlite area ratio can be visually confirmed, for example, by optical microscope photographs. When the pearlite area ratio increases, the area ratio of ledeburite, which is a brittle phase, decreases relatively, and the mechanical properties are improved. The Mn content is preferably in the range of 1.0 to 10.0 mass%, and more preferably in the range of 2.0 to 8.0 mass%. If the Mn content exceeds 10.0 mass%, spattering may occur, which may impair workability and appearance.

[0032] Pearlite is a eutectoid structure that occurs when steel is slowly cooled from the austenite region at C=0.77% by mass in the Fe-C phase diagram to a temperature of 727°C or less. It is a fine layered structure in which very thin plate-like ferrite and cementite are precipitated alternately.

[0033] In addition to promoting the first stage graphitization (graphitization in the austenite region above the A1 transformation point), Nb is likely to form carbides (δ-NbC) as primary crystals, and some of the carbon near the weld is consumed to generate the δ phase, so it has the effect of stabilizing pearlite. However, since excessive generation of the δ phase causes excessive hardening of the weld, the range of 2.0 to 3.0 mass% is preferable.

[0034] Si and Al are more effective than Ni at promoting the graphitization of carbon (C), and are highly effective at lowering the melting point of the weld metal. Therefore, by reducing the difference in melting point between the cast iron base material and the weld metal, they are effective in reducing the area of ​​the affected area that is the source of the formation of brittle microstructures such as levulite. However, the addition of excessive Si and Al increases the risk of weld cracks due to a decrease in the ductility of the weld metal itself, and processing defects when manufacturing the welding material. The Si content is preferably 6.0 mass% or less, and more preferably in the range of 3.0 to 6.0 mass%, and the Al content is preferably 2.0 mass% or less, and more preferably in the range of 1.0 to 2.0%.

[0035] In the present invention, the inevitable components among the constituent elements include Fe, Ti, and the like.

[0036] The repair method of the present invention is characterized in that the above-mentioned welding material for repairing cast iron is used to perform repair welding of a cast iron member.

[0037] When repair welding is performed using a welding material for repairing cast iron, it is also preferable to form a weld between cast iron members and then laminate the welding material at the weld to perform repair welding.

[0038] The microstructure achieved by the repair method of the present invention is characterized in that, when viewed in the microstructure of the heat-affected zone around the weld, the area ratio of pearlite is increased and the amount of ledeburite produced is reduced.

[0039] The microstructure of the heat affected zone of the cast iron base material around or near the weld is improved in that the area fraction of pearlite is increased and the amount of ledeburite formed is reduced in the microstructure of the heat affected zone around the weld, resulting in improved mechanical properties in the heat affected zone. EXAMPLES

[0040] Examples of the present invention will be described below, but the present invention is not limited to these examples.

[0041] (Experiment 1) As shown in Table 2, four types of welding materials, Example 1, Example 2, Comparative Example 1, and Comparative Example 2, were used to fabricate butt joints using spheroidal graphite cast iron (FCD400-18) base material with a plate thickness of 9 mm, and gas tungsten arc welding was performed according to the welding conditions shown in Table 1. In order to simulate the trapezoidal cross-sectional groove (V-shaped) shown in the example of Figure 1, a backing material made of the same material as the base material was used, and a V-shaped groove was made with a root gap of 3 mm and a groove angle of 90°. The chemical compositions of the welding materials are as shown in Table 2. Comparative Example 1 is a Ni-Fe based welding material commercially available as a welding material for cast iron, and Comparative Example 2 is a pure Ni based welding material. The melting point of the welding materials was examined by differential thermal analysis, and the tensile strength, elongation and bead appearance of the welded joints were also examined. The results are shown in Table 2.

[0042] <Tensile test> Tensile test pieces were taken from the butt joints in the direction perpendicular to the weld line, and tensile tests (JIS Z 3121) were performed at a crosshead speed of 1 mm / min.

[0043] [Table 1]

[0044] ·GTAW: Gas Tungsten Arc Welding Welding position: The position of the welded joint when welding Preheat / Interpass Temperature: In principle, preheating is performed during welding. The interpass temperature is the temperature of the base material around the groove just before the next pass is welded in multi-pass welding.

[0045] [Table 2] (evaluation) As shown in the test results in Table 2, good bead appearance was exhibited and good results were obtained for both tensile strength and elongation in Examples 1 and 2. Among them, Example 1 had the highest tensile strength and Example 2 had the highest elongation. On the other hand, in Comparative Examples 1 and 2, although a good bead appearance was exhibited, both the tensile strength and elongation were decreased compared to Examples 1 and 2, and the decrease in elongation was particularly remarkable.

[0046] (Experiment 2) As shown in Table 3, six types of welding materials, namely, Example 3, Example 4, Example 5, Reference Example 1, Reference Example 2, and Reference Example 3, were used to fabricate butt joints using a spheroidal graphite cast iron (FCD400-18) base material with a plate thickness of 9 mm, and gas tungsten arc welding was performed according to the welding conditions shown in Table 1. The chemical compositions of the welding materials are as shown in Table 3, and Reference Examples 1, 2, and 3 are the welding materials prepared. The melting point of the welding materials was examined by differential thermal analysis, and the tensile strength, elongation and bead appearance of the welded joints were also examined. The results are shown in Table 3.

[0047] [Table 3]

[0048] (evaluation) As shown in the test results in Table 3, Examples 3, 4, and 5 exhibited good bead appearance and showed good results in both tensile strength and elongation. Among them, Example 4 had the highest tensile strength and Example 3 had the highest elongation. On the other hand, spattering occurred in Reference Example 1, weld cracks were observed in Reference Example 2, and the metallic luster of the bead disappeared in Reference Example 3, failing to obtain a good bead appearance.

[0049] (Experiment 3) The microstructures at the fusion boundary of seven of the ten types of joints shown in Tables 2 and 3 were examined using optical microscope photographs. The results are shown in Figures 3 to 16.

[0050] Figures 3 and 4 are high- and low-magnification optical microscope photographs of Example 1, Figures 5 and 6 are high- and low-magnification optical microscope photographs of Example 2, Figures 7 and 8 are high- and low-magnification optical microscope photographs of Example 3, Figures 9 and 10 are high- and low-magnification optical microscope photographs of Example 4, Figures 11 and 12 are high- and low-magnification optical microscope photographs of Example 5, Figures 13 and 14 are high- and low-magnification optical microscope photographs of Comparative Example 1, and Figures 15 and 16 are high- and low-magnification optical microscope photographs of Comparative Example 2.

[0051] FIG. 17 is a graph showing the tissue occupancy (area ratio) in each of the detailed microstructure regions of Example 1, Example 2, Example 3, Example 4, Example 5, Comparative Example 1, and Comparative Example 2 shown in FIGS. 3, 5, 7, 9, 11, 13, and 15.

[0052] Furthermore, a graph showing the average thickness (μm) of each of the main microstructure parts in Example 1, Example 2, Example 3, Example 4, Example 5, Comparative Example 1 and Comparative Example 2 shown in Figures 4, 6, 8, 10, 12, 14 and 16 is shown in Figure 18. The average thickness was calculated by dividing the area of ​​each main microstructure in the visual field by the shortest straight line length from the bottom to the top of the visual field.

[0053] In FIG. 3 showing the detailed microstructure of Example 1, structural region 1 is the weld metal (welding material), structural region 2 is graphite, structural region 3 is ledeburite, structural region 4 is pearlite, structural region 5 is bainite and cementite, and the white dashed lines indicate the boundaries between the respective structural regions.

[0054] In the detailed microstructure of Example 1, which had the highest tensile strength of the welded joint, it can be seen that no hard martensite was observed, that ledeburite in structure region 3 was only present in small amounts around the graphite in structure region 2, and that the area ratio of pearlite in structure region 4 was high.

[0055] 4, which shows the main microstructure of Example 1, structure portion 1 is the weld metal (welding material), structure portion 2 is a ledeburite-based structure, and structure portion 3 is a pearlite-based structure, and the white dashed lines indicate the boundaries between the structure portions. It can be seen that the amount of ledeburite-based structure formed in Example 1 is smaller than that in Comparative Example 1 and Comparative Example 2 shown in Figs. 14 and 16.

[0056] In FIG. 5 showing the detailed microstructure of Example 2, structure region 1 is the weld metal (welding material), structure region 2 is graphite, structure region 3 is ledeburite and graphite, structure region 4 is pearlite, and structure region 5 is ferrite and fine pearlite, and the white dashed lines indicate the boundaries between each structure region.

[0057] In the detailed microstructure of Example 2, in which the melting point (melting start temperature) of the welding material was lower than that of Example 1 and the elongation of the welded joint was the highest, no hard martensite was observed, the area of ​​ledeburite in structure region 3 was reduced, the area ratio of pearlite in structure region 4 was high, and soft ferrite also appeared in structure region 5.

[0058] 6, which shows the main microstructure of Example 2, structure portion 1 is the weld metal (welding material), structure portion 2 is a ledeburite-based structure, and structure portion 3 is a pearlite-based structure, and the white dashed lines indicate the boundaries between the structure portions. As in Example 1, it can be seen that Example 2 has a small amount of ledeburite-based structure formed.

[0059] 18, which shows the average thickness of the main microstructure, it can be seen that the average thickness of the ledeburite main structure in Example 2 is smaller than that of Example 1. Therefore, it is considered that the amount of generated ledeburite main structure is also smaller in Example 2 than in Example 1.

[0060] In FIG. 7 showing the detailed microstructure of Example 3, structural region 1 is the weld metal (welding material), structural region 2 is graphite, structural region 3 is ledeburite, structural region 4 is pearlite, structural region 5 is pearlite and ferrite, structural region 6 is ferrite, cementite and martensite, and the black and white dashed lines indicate the boundaries between each structural region.

[0061] In the detailed microstructure of Example 3, ledeburite in structure region 3 is only slightly present around the graphite in structure region 2, and in Fig. 17 which shows the area ratio of the detailed microstructure, it can be seen that the area ratio of ledeburite in structure region 3 is the smallest among Examples 1 to 5. In addition, the area ratio of pearlite in structure region 4 is high, and soft ferrite also appeared in structure regions 5 and 6.

[0062] 8 showing the main microstructure of Example 3, structure portion 1 is the weld metal (welding material), structure portion 2 is a ledeburite-based structure, and structure portion 3 is a pearlite-based structure, and the white dashed lines indicate the boundaries between the structure portions. As in Examples 1 and 2, it can be seen that Example 3 also had a small amount of ledeburite-based structure formed.

[0063] 18, which shows the average thickness of the main microstructure, it is seen that the average thickness of the ledeburite main structure in Example 3 is smaller than those in Examples 1 and 2. Therefore, it is considered that the amount of generated ledeburite main structure is also smaller in Example 3 than in Examples 1 and 2.

[0064] In FIG. 9 showing the detailed microstructure of Example 4, structure region 1 is the weld metal (welding material), structure region 2 is graphite, structure region 3 is ledeburite, structure region 4 is pearlite, and structure region 5 is pearlite and ferrite, and the white lines indicate the boundaries between each structure region.

[0065] The detailed microstructure of Example 4 is similar to that of Examples 1 and 3 in that ledeburite in structure region 3 is present around graphite in structure region 2. On the other hand, in Fig. 17 which shows the area ratio of the detailed microstructure, it can be seen that the area ratio of ledeburite in structure region 3 was the largest among Examples 1 to 5, but was smaller than those of Comparative Example 1 and Comparative Example 2.

[0066] 10 showing the main microstructure of Example 4, structure portion 1 is the weld metal (welding material), structure portion 2 is a ledeburite-based structure, and structure portion 3 is a pearlite-based structure, and the white dashed lines indicate the boundaries between the respective structure portions. The amount of ledeburite-based structure generated in Example 4 appears to be slightly more than in Examples 1 to 3, but is less than in Comparative Examples 1 and 2 shown in FIGS. 14 and 16.

[0067] 18, which shows the average thickness of the main microstructure, it can be seen that the average thickness of the ledeburite main structure in Example 4 was the largest among Examples 1 to 5, but was smaller than those in Comparative Examples 1 and 2.

[0068] In FIG. 11 showing the detailed microstructure of Example 5, structural region 1 is the weld metal (welding material), structural region 2 is graphite, structural region 3 is ledeburite, structural region 4 is pearlite, structural region 5 is pearlite, ferrite, structural region 6 is ferrite, cementite, and martensite, and the white dashed lines indicate the boundaries between each structural region.

[0069] It can be seen that the detailed microstructure of Example 5 has a reduced area ratio of ledeburite compared to Comparative Examples 1 and 2.

[0070] 12 showing the main microstructure of Example 5, structure portion 1 is the weld metal (welding material), structure portion 2 is a ledeburite-based structure, and structure portion 3 is a pearlite-based structure, and the white dashed lines indicate the boundaries between the respective structure portions. It can be seen that the main microstructure of Example 5 has a smaller amount of ledeburite-based structure than Comparative Examples 1 and 2.

[0071] 18, which shows the average thickness of the main microstructure, it can be seen that the average thickness of the ledeburite main structure in Example 5 is the smallest among Examples 1 to 5. Therefore, it is considered that the amount of generated ledeburite main structure in Example 5 is the smallest among Examples 1 to 5.

[0072] In FIG. 13 showing the detailed microstructure of Comparative Example 1, structural region 1 is weld metal, structural region 2 is graphite, structural region 3 is ledeburite, structural region 4 is bainite and pearlite, structural region 5 is bainite and cementite, structural region 6 is martensite and ferrite, and the white dashed lines indicate the boundaries between each structural region.

[0073] In the detailed microstructure of Comparative Example 1, as shown in Fig. 13, a microstructure called ledeburite containing brittle cementite appeared continuously and thickly at the fusion boundary of the heat-affected zone. In Fig. 17 showing the area ratio of the detailed microstructure, it can be seen that the area ratio of ledeburite in structure region 3 in Comparative Example 1 was significantly higher than that in Examples 1 to 5.

[0074] 14 showing the main microstructure of Comparative Example 1, structure portion 1 is the weld metal (welding material), structure portion 2 is a ledeburite-based structure, and structure portion 3 is a pearlite-based structure, and the white dashed lines indicate the boundaries between the structure portions. It can be seen that in Comparative Example 1, the ledeburite-based structure is formed continuously and thickly.

[0075] In FIG. 18 showing the average thickness of the main microstructure, it can be seen that the average thickness of the ledeburite main structure in Comparative Example 1 is significantly higher than those of Examples 1 to 5, and the average thickness of the pearlite main structure is smaller than those of Examples 1 to 5.

[0076] In FIG. 15 showing the detailed microstructure of Comparative Example 2, structural region 1 is weld metal, structural region 2 is graphite, structural region 3 is ledeburite, structural region 4 is pearlite and bainite, structural region 5 is martensite and ferrite, and the black and white dashed lines indicate the boundaries between each structural region.

[0077] The detailed microstructure of Comparative Example 2, in which the melting point (melting start temperature) of the welding material was the highest and the tensile strength and elongation of the welded joint were both the lowest, was similar to that of Comparative Example 1 in that ledeburite in structure portion 3 appeared continuously and thickly at the fusion boundary in the heat-affected zone, as shown in FIG. 15 .

[0078] 16, which shows the main microstructure of Comparative Example 2, structure portion 1 is the weld metal (welding material), structure portion 2 is a ledeburite-based structure, and structure portion 3 is a pearlite-based structure, and the white dashed lines indicate the boundaries between the structure portions. As in Comparative Example 1, it can be seen that in Comparative Example 2, a thick, continuous ledeburite-based structure is formed.

[0079] In FIG. 18 showing the average thickness of the main microstructure, it can be seen that the average thickness of the ledeburite main structure in Comparative Example 2 is significantly higher than those of Examples 1 to 5, as in Comparative Example 1, and the average thickness of the pearlite main structure is smaller than those of Examples 1 to 5.

[0080] As described above, in the microstructure at the fusion boundary shown in Figs. 3 to 16, as shown in Figs. 17 and 18, it was found that the area ratio of pearlite was increased and the amount of ledeburite generated was reduced at the fusion boundary when the welding material of the present invention was used, and the microstructure was improved. [Explanation of symbols]

[0081] 11 Cast iron base material 12 Welding materials 13 Welding 14 Weld boundary 15 Defective part 16 Backing plate

Claims

1. A welding material for repair welding of cast iron members, A welding material for repairing cast iron, comprising at least Ni, Cr, Mn and Nb.

2. 2. The welding material for repairing cast iron according to claim 1, characterized in that it is composed of 10.0 to 30.0 mass% of Cr, 1.0 to 10.0 mass% of Mn, 2.0 to 3.0 mass% of Nb, and the balance being Ni and unavoidable components.

3. 3. The welding material for repairing cast iron according to claim 2, further comprising, as optional added elements, up to 6.0 mass% Si and up to 2.0 mass% Al.

4. A repair method for a cast iron member, comprising the steps of: repair welding the cast iron member using the welding material for repairing cast iron according to claim 1, 2 or 3.

5. 5. The repair method according to claim 4, wherein the repair welding is build-up repair or back plate repair.

6. 5. The repair method according to claim 4, further comprising increasing the area ratio of pearlite and reducing the amount of ledeburite formed in the microstructure of the heat-affected zone around the weld.

Citation Information

Patent Citations

  • Uncoated electric welding electrode for high-chromium cast iron repair welding

    CN102618778A

  • Grinding roller manufacturing / remanufacturing abrasion-resistant material and preparation method thereof

    CN106238709A

  • Production method of wear-resistant impact-resistant tamping pickaxe

    CN110405330A

  • Alloy powder for agricultural machine part cladding wear-resistant layer

    CN110551938A

  • Method for repairing metallic alloy member

    JP1998137976A